Effect Of Motivation and Job Satisfaction on Employee Performance at PT Catur Putraharmoni - Ikhsan Amar Jusman; Sultan Iskandar; Manda HM (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
This study aims to determine the motivation and job satisfaction have a significant positive effect partially or simultaneously on the performance of employees of PT. Chess Putraharmony. This research was conducted by distributing questionnaires to 82 respondents. This type of research is quantitative research with a sampling technique is stratified proportional random sampling. The data analysis technique in this study used multiple linear regression analysis techniques. The results obtained from this study are motivation and job satisfaction has a significant positive effect partially or simultaneously on the performance of employees of PT. Catur Putraharmoni.